Follow-up study after intracranial percutaneous transluminal cerebral balloon angioplasty. - Mori, T; Fukuoka, M; Kazita, K; Mori, K (American Journal of Neuroradiology, 1998)
BACKGROUND AND PURPOSE Our objective was to find the specific angiographic characteristics of atherosclerotic lesions that indicate suitability for intracranial percutaneous transluminal cerebral balloon angioplasty (PTCBA).METHODS Forty-two clinically symptomatic patients with 42 hemodynamically significant intracranial lesions (>70% stenosis) were treated by PTCBA between January 1992 and May 1996. Before treatment, the patients were assigned to three groups according to the angiographic characteristics of the lesions, as follows: type A, short (5 mm or less in length) concentric or moderately eccentric lesions less than totally occlusive; type B, tubular (5 to 10 mm in length), extremely eccentric or totally occluded lesions, less than 3 months old; and type C, diffuse (more than 10 mm in length), extremely angulated (>90 degrees) lesions with excessive tortuosity of the proximal segment, or totally occluded lesions, and 3 months old or older. The patients were followed up for a period of 1 month to 6 years to compare the results of PTCBA treatment among the three groups. Primary end points were death, stroke, or bypass surgery.RESULTS The clinical success rates for the type A, B, and C groups were 92%, 86%, and 33%, respectively. Cumulative risks of fatal or nonfatal ischemic stroke or ipsilateral bypass surgery in type A, B, and C groups were 8%, 26%, and 87%, respectively. The cumulative risk of 8% among patients in the type A group appeared to be smaller than in studies reported in the literature.CONCLUSION PTCBA for intracranial simple (type A) lesions yields a favorable clinical outcome for symptomatic patients.